2023
DOI: 10.3390/nano13040647
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hydrogen Storage Media by g-CN Monolayer Decorated with NLi4: A First-Principles Study

Abstract: A two-dimensional graphene-like carbon nitride (g-CN) monolayer decorated with the superatomic cluster NLi4 was studied for reversible hydrogen storage by first-principles calculations. Molecular dynamics simulations show that the g-CN monolayer has good thermal stability at room temperature. The NLi4 is firmly anchored on the g-CN monolayer with a binding energy of −6.35 eV. Electronic charges are transferred from the Li atoms of NLi4 to the g-CN monolayer, mainly due to the hybridization of Li(2s), C(2p), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The facile and adjustable chemical composition thus increases the demand of its application in supercapacitors. [21] Besides, when MOFs work as a template, the larger specific surface area and consequently their short electrochemically active pathways can be inherited, leading to an increase in the specific capacitance and structural robustness in long-term cyclability. [22] For example, Cheng et al synthesized hierarchical MOFs-derived NiCo 2 S 4 @Mo-doped Co-LDH arrays and applied them in supercapacitors, as illustrated in Figure 3a.…”
Section: Supercapacitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The facile and adjustable chemical composition thus increases the demand of its application in supercapacitors. [21] Besides, when MOFs work as a template, the larger specific surface area and consequently their short electrochemically active pathways can be inherited, leading to an increase in the specific capacitance and structural robustness in long-term cyclability. [22] For example, Cheng et al synthesized hierarchical MOFs-derived NiCo 2 S 4 @Mo-doped Co-LDH arrays and applied them in supercapacitors, as illustrated in Figure 3a.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…[22] For example, Cheng et al synthesized hierarchical MOFs-derived NiCo 2 S 4 @Mo-doped Co-LDH arrays and applied them in supercapacitors, as illustrated in Figure 3a. [21] They first synthesized NiCo 2 S 4 nanowire@ZIF-67 core-shell structure and then etched it at room temperature. The as-prepared Co-LDH exhibited the nanosheet morphology.…”
Section: Supercapacitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Creating a qualitative link between structural attributes and functional characteristics provides valuable guidance for the development of novel energy storage materials. However, the comprehensive characterization of adsorption performance through experimental methods remains challenging and expensive for researchers. Therefore, utilizing systematic computational studies will be instrumental in the initial evaluation of the newly proposed materials. In the recent studies conducted by Qi et al, it was observed that a novel 2D material, g-B 5 N 3 , demonstrates heightened carrier mobility and outstanding optical performance . Expanding upon the analysis of its electronic properties, we propose that it represents a promising candidate for applications in hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%